1998
DOI: 10.1016/s0960-9822(98)70276-3
|View full text |Cite
|
Sign up to set email alerts
|

Thymic skewing of the CD4/CD8 ratio maps with the T-cell receptor α-chain locus

Abstract: The thymic preference for CD4+ T cells over CD8+ T cells is often attributed to a default pathway favouring CD4+ T cells or to homeostatic mechanisms. It is also clear, however, that T-cell receptor (TCR) preferences for major histocompatibility complex (MHC) class I versus class II binding will strongly influence an individual clone's skewing to the CD4 or CD8 subset. The variable region of each TCR alpha chain (V alpha) studied to date is found to be overrepresented in either CD4+ or CD8+ cells, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 27 publications
2
29
1
Order By: Relevance
“…In some mouse combinations, this trait was mapped to the TCR␣ chain locus, suggesting that it was the consequence of a preference for MHC class II selection by a given array of V␣ genes characterizing a TCR␣ haplotype (33). However, the higher CD4/CD8 T cell ratio in DBA/2 as compared with C57BL/6 mice was not linked to either TCR␣ or TCR␤ loci, and was independent of MHC haplotype (20).…”
Section: Discussionmentioning
confidence: 99%
“…In some mouse combinations, this trait was mapped to the TCR␣ chain locus, suggesting that it was the consequence of a preference for MHC class II selection by a given array of V␣ genes characterizing a TCR␣ haplotype (33). However, the higher CD4/CD8 T cell ratio in DBA/2 as compared with C57BL/6 mice was not linked to either TCR␣ or TCR␤ loci, and was independent of MHC haplotype (20).…”
Section: Discussionmentioning
confidence: 99%
“…Sim et al 14 showed that the ratios of these cells are affected in the thymus by genes mapping to the TCR␣ locus. Several recent publications have shown that the size of the CD8 + population in the thymus can be increased by increased expression of proteins thought to improve lymphocyte survival such as notch 23 and bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 3 and 4 present the results of these scans for the relevant chromosomes together with results for chromosomes 14 (TCR␣) and 6 (TCR␤), which have been implicated in control of CD4:CD8 ratio by previous scans. 14 Two genomic segments significantly associated with CD4:CD8 ratios in peripheral organs were identified, based on criteria established by Lander and Kruglyak. 22 The first, designated Trmq1 (for T cell ratio modifier QTL 1), mapped to the telomeric end of c6 (peak marker D6Mit15 at 74 cM) and was found in the F2 cross ( Figure 3b).…”
Section: Linkage Analysis Of Loci Impacting Cd4:cd8 Ratios In the Permentioning
confidence: 99%
See 2 more Smart Citations